Chimerism in Myeloid Malignancies following Stem Cell Transplantation Using FluBu4 with and without Busulfan Pharmacokinetics versus BuCy - Shatha Farhan; Michael Bazydlo; Klodiana Neme; Nancy Mikulandric; Edward Peres; Nalini Janakiraman (Advances in Hematology)
In the era of precision medicine, the impact of personalized dosing of busulfan is not clear. We undertook a retrospective analysis of 78 patients with myeloid malignancies who received fludarabine and busulfan (FluBu4) with or without measuring Bu pharmacokinetics (Bu PK) and those who received busulfan with cyclophosphamide (BuCy). Fifty-five patients received FluBu4, of whom 21 had Bu PK measured, and 23 patients received BuCy. Total donor cell chimerism showed that the percentage of patients maintaining 100% donor chimerism on day 100 was 66.7%, 38.2%, and 73.9% in the FluBu4 with PK, FluBu4 with no PK, and BuCy, respectively (P = .001). Patients who had decreasing donor chimerism by day 100 were 23.8%, 52.9%, and 26.1% in the FluBu4 with PK, FluBu4 with no PK, and BuCy, respectively (P = .04). Bu PK group had fewer patients with less than 95% donor chimerism on day 30, which was not statistically significant, 5% (FluBu4 PK), 31% (FluBu4 with no PK), and 21% (BuCy) (P = .18). Survival distributions were not statistically significant (P = .11). Thus, personalized drug dosing can impact donor chimerism in myeloid malignancies. This will need to be examined in larger retrospective multicenter studies and prospective clinical trials.